2013
DOI: 10.3855/jidc.2900
|View full text |Cite
|
Sign up to set email alerts
|

Faecal carriage of ESBL-producing Enterobacteriaceae and carbapenem-resistant Gram-negative bacilli in community settings

Abstract: Introduction: The aim of this study was to determine the prevalence of intestinal carriage of extended-spectrum beta-lactamase (ESBL)-producing Enterobacteriaceae and carbapenem-resistant Gram-negative bacilli in the community in Buenos Aires, Argentina. Methodology: Faecal samples from 164 non-hospitalized patients were cultured on CHROMagar KPC and CHROMagar ESBL plates. Isolates resistant to third-generation cephalosporins or carbapenems were selected for further study. The minimal inhibitory concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 19 publications
3
27
0
Order By: Relevance
“…Similar increases were found in southern Europe, with Greece reporting an incidence of carbapenem resistance upwards of 60% in K. pneumoniae isolates for 2014 [28]. Recent studies have identified a high prevalence (16–19%) of ESBL-producing GNB in community settings [29]. With carbapenemases following similar plasmid-mediated genetic exchange as ESBLs, there has been a call for further research on the spread of CRE into community settings owing to the highly transmissible nature of carbapenemase-producing genetic elements [25].…”
Section: Epidemiology Of Carbapenem Resistancementioning
confidence: 57%
See 3 more Smart Citations
“…Similar increases were found in southern Europe, with Greece reporting an incidence of carbapenem resistance upwards of 60% in K. pneumoniae isolates for 2014 [28]. Recent studies have identified a high prevalence (16–19%) of ESBL-producing GNB in community settings [29]. With carbapenemases following similar plasmid-mediated genetic exchange as ESBLs, there has been a call for further research on the spread of CRE into community settings owing to the highly transmissible nature of carbapenemase-producing genetic elements [25].…”
Section: Epidemiology Of Carbapenem Resistancementioning
confidence: 57%
“…Urine was the primary source of isolates [16,25,35,37,40,43], followed by faeces [29,41,45,46], intra-abdominal fluid [38,39,44], blood [42] and respiratory culture [36]. For the five studies only including CRE, K. pneumoniae was the most common organism [16,25,36,37], except a US-based study that had a slightly higher percentage of Enterobacter spp.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study shows that 19.8% of E.coli isolates from fecal specimens of Lebanese patients with diarrhea were ESBL-producers .This result is similar to other recent reported studies from other continents . For example a study from Argentina in 2012, showed that the carrier rate of ESBL-positive E. coli strains in the fecal flora was 17.0% [26], while the study from Libya in 2014, demonstrated the prevalence of ESBL-producing E. coli at 13.4% [27]. In addition, our study indicated that bla CTX-M gene was predominant (85%), followed by the bla TEM (50%) and bla OXA (6%) genes, whereas the bla SHV , bla PER and bla GES were absent in our E.coli isolates.…”
Section: Discussionmentioning
confidence: 99%